MOBILE-BASED LAUNDRY ORDERING SYSTEM WITH OPENSTREETMAP INTEGRATION FOR CUSTOMER COORDINATE CAPTURE - Muhammad Khaerudin; Khabibillah Khabibillah; Dedi Setiadi; Tata Sumitra; Dimpo Sinaga (Jurnal Ilmiah METADATA, 2026)
Advances in information technology have driven digital transformation across various service sectors, including the laundry industry. Conventional laundry services still face a number of challenges, such as inefficient ordering processes, difficulties in accurately determining customer locations, and the lack of an integrated service monitoring system. This study aims to develop a mobile-based laundry ordering information system that utilizes OpenStreetMap to obtain accurate, real-time customer coordinates. The developed system allows customers to place orders online, specify pickup locations via a digital map, and monitor service status in real time. Meanwhile, service providers can optimize pickup and delivery processes based on location data obtained from the system. The results indicate that the developed system enhances operational efficiency, location accuracy, and service quality. The integration of OpenStreetMap provides flexibility in managing open geospatial data and supports the development of large-scale systems. Additionally, this system adopts the concept of location-based services, which aligns with current mobile technology trends.